(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2025)
Unidentified bodies pose substantial challenges in forensic and medico-legal investigations, requiring a thorough and multidisciplinary approach. This case report discusses the forensic investigation of an unidentified male, approximately 40 years old, discovered deceased on the railway tracks. In this case, severe traumatic injuries were observed, particularly to the head and face, suggesting a high-impact collision, likely with a moving train. However, the absence of personal identification documents complicated the process of establishing the individual’s identity. The forensic examination revealed multiple traumatic injuries, including a crushed head, fractures in the upper limbs, and significant abdominal lacerations. Internal findings such as congested organs, ruptured spleen, and lacerated liver supported the high-impact trauma hypothesis. The presence of post-mortem staining and rigor mortis provided further insight into the timing of death. Notably, a tattoo in Urdu and circumcision suggested the deceased’s religious background, aiding in preliminary identification efforts. This case highlights the complexities involved in distinguishing between pre- and post-mortem injuries and emphasizes the importance of forensic techniques such as DNA profiling and dental record comparisons in resolving cases involving unknown victims. The investigation underscores the need for a comprehensive, multidisciplinary approach to railway fatalities, combining scene analysis, autopsy, and ancillary testing to determine the cause of death and support identification efforts. Such cases necessitate coordinated efforts among forensic experts, law enforcement, and medical examiners.